Respuesta :

Answer:

y = -x +3

Step-by-step explanation:

first find the slope

m = (y2-y1) / (x2-x1)

m = (5-1) / (2--2)  = -1

note that it does not matter which points you chose to be second or first

use point-slope equation

y - y1 = m ( x - x1 )

y - 1 = -1 ( x - 2)

y = -x +2 + 1

y = -x +3

please if you find my answer helpful mark it brainiest

Answer:

y=-x+3

Step-by-step explanation:

Gradient(m)= y1-y2÷x1-x2

=1-5÷2-(-2)

=-4÷4

=-1

therefore m= -1

y-y1=m(x-x1)

y-1=-1(x-2)

y=-x+2+1

y=-x+3